THE IMPACT OF SUPERFICIAL DERMATOPHYTOSIS ON QUALITY OF LIFE IN A RURAL POPULATION: A CROSS-SECTIONAL OBSERVATIONAL STUDY - Ruchika tripathi,; Uday prabhakar,; Rajaram yadav, (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The present study aims at measuring the impact of the disease on the quality of life (QoL) of the patients and its relation to the number of relapses in the disease course and the socio-economic status (SES) of the patients. Methods: The study was a cross-sectional study that was undertaken for a period of 6 months. A total of 100 patients aged 16 or more were enrolled with clinically and microscopically proven dermatophytosis of the skin and evaluated for impact on QoL using the dermatology life quality index (DLQI) questionnaire. A modified BG Prasad scale was used for assessing the SES of the study subjects. Statistical analysis was performed using the t-test to determine the impact of dermatophytosis on QoL, and the correlation of DLQI scores with the number of relapses and SES of the patients was also assessed. Results: The majority of patients (80%) reported to have a moderate to very large impact on QoL due to tinea. The DLQI was found to be significantly associated with the number of relapses (p=0.023). However, no significant association was seen with socioeconomic class (p=0.670). Conclusion: Superficial dermatophytosis has a large effect on the QoL of the patients, and it impacts their lives adversely, leading to psychological and social problems.